2008
DOI: 10.1177/0269215508095089
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the agreement between clinical, biomechanical and neurophysiological measures of spasticity

Abstract: The presentations of spasticity are variable and are not always consistent with existing definitions. Existing clinical scales that depend on the quantification of muscle tone may lack the sensitivity to quantify the abnormal muscle activation and stiffness associated with common definitions of spasticity. Neurophysiological measures may provide more clinically useful information for the management and assessment of spasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 15 publications
4
118
1
3
Order By: Relevance
“…Although Voerman et al [51] reported that RTPM parameters were not significantly different between patients with spasticity and non-disabled individuals, Pandyan et al [49] found significant differences in RTPM parameters between affected and contralateral sides of people with spastic hemiparesis. Voerman et al [51] reported positive correlations of RTPM and MAS only at low speed testing ( ¼ 0.73, p50.05), whereas two other studies did not find any significant associations between MAS scores, RTPM and EMG parameters [48,50]. Pandyan et al [50] did find that EMG parameters were significantly different during slow and fast speed stretching but Voerman et al [51] showed that EMG responses were significantly different between patients post-stroke and non-disabled subjects.…”
Section: Force/torque Measurementsmentioning
confidence: 98%
See 2 more Smart Citations
“…Although Voerman et al [51] reported that RTPM parameters were not significantly different between patients with spasticity and non-disabled individuals, Pandyan et al [49] found significant differences in RTPM parameters between affected and contralateral sides of people with spastic hemiparesis. Voerman et al [51] reported positive correlations of RTPM and MAS only at low speed testing ( ¼ 0.73, p50.05), whereas two other studies did not find any significant associations between MAS scores, RTPM and EMG parameters [48,50]. Pandyan et al [50] did find that EMG parameters were significantly different during slow and fast speed stretching but Voerman et al [51] showed that EMG responses were significantly different between patients post-stroke and non-disabled subjects.…”
Section: Force/torque Measurementsmentioning
confidence: 98%
“…Through biomechanical modeling, the reactive forces recorded during slow and fast velocities are used to estimate elastic, viscous, and neural components of the resistance [29]. (ii) A force transducer and an electrogoniometer record the reactive forces and joint angles imposed by manual slow and fast ramp stretches [48][49][50][51]. The RTPM, which is difference between slope of the force-angle curve from slow and fast stretches obtained using linear regression techniques, is used as an index of spasticity [48][49][50][51].…”
Section: Pendulum Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The few tests that address orofacial tone impairments instruct the clinician to passively stretch [14] or palpate [15] the muscles of interest and then rate whether resistance to the perturbation is lower or higher than normal. A paucity of normative data for perceptual measures of tone combined with poor correlation between clinical rating scale scores and physiologic measures of spasticity [16] limits the reliability and clinical utility of perceptual ratings of tone.…”
Section: Introductionmentioning
confidence: 99%
“…Há estudos que afirmam que a relação da eletromiografia com a escala de Ashworth é baixa (69) . Os resultados de estudos recentes mostram que as características metodológicas da EAm não são satisfatórias e que a EAm não deve ser usada como uma medida de resultado único para a avaliação da espasticidade.…”
Section: Discussão Das Análises Complementares (Componentes Principais)unclassified